2016
DOI: 10.1007/s11258-016-0695-5
|View full text |Cite
|
Sign up to set email alerts
|

Does fire affect the temporal pattern of trophic resource supply to pollinators and seed-dispersing frugivores in a Brazilian savanna community?

Abstract: In tropical savannas, such as the campo cerrado in Brazil, fire plays an important role, affecting plant species' life history. Since fire has the potential to modify the structure of savanna communities as a whole, it is expected that it may influence the resource supply for mutualists by altering the pattern of investment in sexual reproduction. We used an experimental approach to test if fire alters trophic resource availability to pollinators (nectar, pollen, and oil) and seed-dispersing frugivores (fleshy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
0
3
0
1
Order By: Relevance
“…Competition and disturbance can affect flowering time and duration (Rathcke & Lacey ), and density can influence both animal and plant reproductive timing (Schmitt ; Ávila et al ). Burning can lengthen flowering time in fire‐adapted landscapes (Mola & Williams ), and heterogeneous fire severity and intensity (“pyrodiversity”) across a landscape may further lengthen the flowering season (Tunes et al ). Finally, directly planting or placing nesting habitat across heterogeneous microclimates can also extend timing of populations (see Technique 2 ‐ Utilizing Microclimate Heterogeneity).…”
Section: Introductionmentioning
confidence: 99%
“…Competition and disturbance can affect flowering time and duration (Rathcke & Lacey ), and density can influence both animal and plant reproductive timing (Schmitt ; Ávila et al ). Burning can lengthen flowering time in fire‐adapted landscapes (Mola & Williams ), and heterogeneous fire severity and intensity (“pyrodiversity”) across a landscape may further lengthen the flowering season (Tunes et al ). Finally, directly planting or placing nesting habitat across heterogeneous microclimates can also extend timing of populations (see Technique 2 ‐ Utilizing Microclimate Heterogeneity).…”
Section: Introductionmentioning
confidence: 99%
“…), or experimental burning (Tunes et al. ). Overall, heterogeneous fire regimes appear to increase pollinator diversity (Ponisio et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found a range of positive to negative effects of fire on pollinator communities using space-for-time substitutions (Ne'eman et al 2000, Potts et al 2001, Moretti et al 2009, Grundel et al 2010, prescribed burn history (Campbell et al 2007, Nuland et al 2013, or experimental burning (Tunes et al 2016). Overall, heterogeneous fire regimes appear to increase pollinator diversity (Ponisio et al 2016), but explanations for why some bee species respond positively to fire are largely undeveloped.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effects of biotic elements are frequently mixed up by prevailing abiotic factors, as demonstrated by Rodríguez-Pérez and Traveset (2016) and Tunes et al (2017).…”
Section: Introductionmentioning
confidence: 99%